Coastal Forest Seawater Exposure Increases Stem Methane Concentration. Issue 2 (13th February 2021) - Norwood, Matthew J.; Ward, Nicholas D.; McDowell, Nate G.; Myers‐Pigg, Allison N.; Bond‐Lamberty, Ben; Indivero, Julia; Pennington, Stephanie; Wang, Wenzhi; Kirwan, Matt; Hopple, Anya M.; Megonigal, J. Patrick
Abstract: Methane (CH4 ) exchange between trees and the atmosphere has recently emerged as an important, but poorly quantified process regulating global climate. The sources (soil and/or tree) and mechanisms driving the increase of CH4 in trees and degassing to the atmosphere are inadequately understood, particularly for coastal forests facing increased exposure to seawater. We investigated the eco‐physiological relationship between tree stem wood density, soil and stem oxygen saturation (an indicator of redox state), soil and stem CH4 concentrations, soil and stem carbon dioxide (CO2 ) concentrations, and soil salinity in five forests along the United States coastline. We aim to evaluate the mechanisms underlying greenhouse gas increase in trees and the influence of seawater exposure on stem CH4 accumulation. Seawater exposure corresponded with decreased tree survival and increased tree stem methane. Tree stem wood density was significantly correlated with increased stem CH4 in seawater exposed gymnosperms, indicating that dying gymnosperm trees may accumulate higher levels of CH4 in association with seawater flooding. Further, we found that significant differences in seawater exposed and unexposed gymnosperm tree populations are associated with increased soil and stem CH4 and CO2, indicating that seawater exposure significantly impacts soil and stem greenhouse gas abundance. Our results provide new insight into the potential mechanisms driving tree CH4 accumulation within gymnosperm coastal forests. Plain Language Summary: Trees emit greenhouse gases such as methane and carbon dioxide to the atmosphere. The origin of these gases includes production in the tree or in the surrounding soils. Disturbances to these systems, such as seawater exposure that increases soil salinity, have an unknown impact on gas production and connectivity between soil and trees. We found that higher soil salinities corresponded to higher soil methane content and increased stem methane. The accumulation of soil and tree methane was lower in sites with no salinity exposure and higher in sites with high salinity. As coastal systems become more vulnerable to changes in seawater exposure, this may have consequences on methane emitted from trees to the atmosphere. Key Points: Seawater exposure significantly increased internal stem CH4 concentration There is a significant correlation between stem wood density and stem CH4 concentration Low stem and soil O2 were significantly linked to seawater exposure and decreased tree survival